Multifaceted biological insights from a draft genome sequence of the tobacco hornworm moth, Manduca sexta. (September 2016) - Kanost, Michael R.; Arrese, Estela L.; Cao, Xiaolong; Chen, Yun-Ru; Chellapilla, Sanjay; Goldsmith, Marian R.; Grosse-Wilde, Ewald; Heckel, David G.; Herndon, Nicolae; Jiang, Haobo; Papanicolaou, Alexie; Qu, Jiaxin; et al.
Abstract: Manduca sexta, known as the tobacco hornworm or Carolina sphinx moth, is a lepidopteran insect that is used extensively as a model system for research in insect biochemistry, physiology, neurobiology, development, and immunity. One important benefit of this species as an experimental model is its extremely large size, reaching more than 10 g in the larval stage. M. sexta larvae feed on solanaceous plants and thus must tolerate a substantial challenge from plant allelochemicals, including nicotine. We report the sequence and annotation of the M. sexta genome, and a survey of gene expression in various tissues and developmental stages. The Msex_1.0 genome assembly resulted in a total genome size of 419.4 Mbp. Repetitive sequences accounted for 25.8% of the assembled genome. The official gene set is comprised of 15, 451 protein-coding genes, of which 2498 were manually curated. Extensive RNA-seq data from many tissues and developmental stages were used to improve gene models and for insights into gene expression patterns. Genome wide synteny analysis indicated a high level of macrosynteny in the Lepidoptera. Annotation and analyses were carried out for gene families involved in a wide spectrum of biological processes, including apoptosis, vacuole sorting, growth and development, structures of exoskeleton, egg shells, and muscle, vision, chemosensation, ion channels, signal transduction, neuropeptide signaling, neurotransmitter synthesis and transport, nicotine tolerance, lipid metabolism, and immunity. This genome sequence, annotation, and analysis provide an important new resource from a well-studied model insect species and will facilitate further biochemical and mechanistic experimental studies of many biological systems in insects. Graphical abstract: Highlights: The genome of Manduca sexta was sequenced and assembled, with a total genome size of 419.4 Mbp. 15, 451 protein-coding genes were annotated, and 2498 of these were manually curated. RNA-seq data from many tissues and developmental stages informed the gene models and provide insights into gene expression patterns. Gene families for a broad set of topics in M. sexta biology were analyzed.